Solar-based irrigation systems as a game changer to improve agricultural practices in Sub-Sahara Africa: a case study from Mali - Birhanu, B.Z.; Sanogo, K.; Traoré, S.S.; Minh, Thai Thi; Kizito, Fred (Frontiers Media, 2023)
Introduction: In rainfed agricultural systems, sustainable and efficient water management practices are key to improved agricultural productivity and natural resource management. The agricultural system in sub-Saharan Africa (SSA) relies heavily on the availability of rainfall. With the erratic and unreliable rainfall pattern associated with poor and fragile soils, agricultural productivity has remained very low over the years. Much of the SSA agricultural land has been degraded with low fertility as a result of ongoing cultivation and wind and water erosion. This has resulted in an increased food shortage due to the ever-increasing population and land degradation. Better agricultural and nutritional security are further hampered by the lack of reliable access to the available water resources in the subsurface hydrological system. Methods: This study used socio-economic data from 112 farm households and Boolean and Fuzzy methods to understand farmers' perceptions and identify suitable areas to implement Solar Based Irrigation Systems (SBISs) in the agro-ecologies of Bougouni and Koutiala districts of southern Mali. Results and discussion: Results revealed that the usage of SBISs has been recent (4.5 years), majorly (77%) constructed by donor-funded projects mainly for domestic water use and livestock (88%). With regards to irrigation, vegetable production was the dominant water use (60%) enabling rural farm households to gain over 40% of extra household income during the dry season. Results further showed that 4,274 km2 (22%) of the total land area for the Bougouni district, and 1,722 km2 (18%) of the Koutiala district are suitable for solar-based irrigation. The affordability of solar panels in many places makes SBISs to be an emerging climate-smart technology for most rural Malian populations.